Conceptualization of Organized Crime and its regulation in Colombian Criminal Legislation (2019)
Organized Crime, as a current phenomenon, has been studied not only in each country that suffers these crimes, but also by international laws, which allow us to outline a concept adaptable to the social reality of each nation. For Colombia, the constructi